Perencanaan Jaringan Perpipaan Kawasan Tumbuh Kembang Perumahan Desa Logandeng Kabupaten Gunungkidul Menggunakan Aplikasi Epanet 2.0 - Tito Ghazy Aflah; Sri Hastutiningrum; Soedarsono Soedarsono (Jurnal Serambi Engineering, 2022)
According to data from PDAM Tirta Handayani, Gunungkidul Regency, as the manager of clean water providers in Wonosari City and its surroundings, currently only able to serve about 76% of the total population in the service area, mostly through direct lines. Condition Currently, there are still many obstacles in drinking water services, especially in terms of distribution to customer. The purpose of the study was to determine the required discharge in housing and Knowledge of pipeline network planning. This research is located in the housing that will be built in Logandeng village, Gunungkidul district. Data were collected including debits, hours peak water use, and look at the topography of the planning area as an observation technique in data input, besides that, interview techniques are also used to be able to find out the number of houses and population in the housing planning area. Based on calculation analysis and epanet simulations in planning the clean water distribution network in housing that will be built in the village of Logandeng, in planning the distribution pipe network system using gravity drainage system, the highest elevation here is 206 MDPL and the lowest is 188 MDPL, so that the debits in the planning system still reach planning with branch system. Water demand in Logandeng housing in 2021 is 0.921 L/second with a population of 511 people, while in 2025 it is 1.188 L/second with population of 664 people.